Ethnic Differences in Family Childcare Providers' Nutrition- and Activity-Related Attitudes and Barriers - Qianxia Jiang; Alison Tovar; Patricia M. Risica; Kristen Cooksey Stowers; Marlene Schwartz; Caitlin Lombardi; Augustine Kang; Noereem Z. Mena; Kim M. Gans (Hindawi Limited, 2021)
Objective. The aim of the study is to examine family childcare providers' (FCCPs) attitudes and perceived barriers related to nutrition, physical activity (PA), and screen time (ST) behaviors of preschool children, exploring differences by provider ethnicity. Design. Baseline survey data from a cluster-randomized trial. Participants. Around 168 FCCPs completed a telephone survey, and 126 completed both telephone and in-person surveys. Main Outcome Measures. Phone and in-person surveys include 44 questions to assess FCCPs attitudes and perceived barriers regarding nutrition, PA, and ST in the family childcare home. Analysis. Associations by ethnicity (Latinx vs. non-Latinx) were assessed by ANOVA, adjusting for provider education and Bonferroni correction. Results. Some FCCP attitudes were consistent with national obesity prevention guidelines; for example, most FCCPs agreed that they have an important role in shaping children's eating and PA habits. However, many FCCPs agreed with allowing children to watch educational TV and did not agree that children should serve themselves at meals. Adjusting for education, there were statistically significant differences in attitude and perceived barrier scores by provider ethnicity. For example, Latinx FCCPs were more likely to agree that they should eat the same foods as childrenp<.001 but less likely to agree that serving the food at meal and snack time is the adult's responsibility p<.001. Latinx FCCPs were more like to perceive barriers related to children's safety playing outside p<.001. Conclusions and Implications. While FCCPs hold some nutrition-, PA-, and ST-related attitudes consistent with national guidelines, training opportunities are needed for FCCPs to improve knowledge and skills and overcome perceived barriers related to nutrition and PA. Latinx FCCPs, in particular, may need culturally tailored training and support to overcome misperceptions and barriers.